1991
DOI: 10.1210/endo-128-1-331
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia-Induced Inhibition of Magnocellular Neurons Causes Stressor-Selective Impairment of Stimulated Adrenocorticotropin Secretion in Rats*

Abstract: Chronically hyponatremic rats were subjected to various stressors in order to evaluate the possible contribution of magnocellular neurons to the regulation of ACTH secretion, since such rats have markedly inhibited secretion and synthesis of magnocellular arginine vasopressin (AVP) and oxytocin (OT). Stress caused by a novel environment or by insulin-induced hypoglycemia resulted in moderate increases in plasma ACTH, which were of similar magnitude in both hyponatremic and normonatremic rats, and these stresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 52 publications
5
34
0
Order By: Relevance
“…Posm was normalized before the cold pressor ( Table 2), so that concurrent hypoosmolemia/hyponatremia per se can be excluded. Pre-infusion osmolality was negatively correlated with the AVP response, consistent with the recognized blunting effects of chronic hyponatremia on AVP and ACTH responses, (Dohanics et al, 1991;Goldman et al, 1996;Robertson, 2001). Thus the role of long-standing hyponatremia can also be discounted, though inclusion of a non-psychiatric control group with hyponatremia would more definitively address this possibility.…”
Section: Discussion Divergent Neuroendocrine Responses To the Cold Prsupporting
confidence: 63%
“…Posm was normalized before the cold pressor ( Table 2), so that concurrent hypoosmolemia/hyponatremia per se can be excluded. Pre-infusion osmolality was negatively correlated with the AVP response, consistent with the recognized blunting effects of chronic hyponatremia on AVP and ACTH responses, (Dohanics et al, 1991;Goldman et al, 1996;Robertson, 2001). Thus the role of long-standing hyponatremia can also be discounted, though inclusion of a non-psychiatric control group with hyponatremia would more definitively address this possibility.…”
Section: Discussion Divergent Neuroendocrine Responses To the Cold Prsupporting
confidence: 63%
“…For example, electrical stimulation of the SON has been demonstrated to increase plasma corticosterone in anesthetized rats (37). Also, an attenuated stress-induced rise in plasma ACTH was found in hyponatremic rats (12) and after peripheral immunoneutralization of OXT (20), indicating the involvement of magnocellular AVP and /or OXT in HPA axis regulation. Similarly, local osmotic stimulation of the SON of conscious rats increased not only local and peripheral AVP and OXT release but also elevated ACTH secretion into blood (62; for a review, see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…As OXT is locally released within the SON and PVN, for example, during swim stress (57,61), and OXT receptors have been identified within these hypothalamic nuclei (2,5,19,31), we aim to more specifically reveal local OXT actions on basal and stress-induced HPA axis activity. We hypothesize OXT actions on HPA axis functions would occur predominantly within the PVN, but likely also within the SON, as a significant contribution of magnocellular SON neurons to the regulation of HPA axis activity has repeatedly been shown (12,20,37,62, for a review, see Ref. 16).…”
mentioning
confidence: 97%
“…21). Several studies report 5-to lO-fold increases of OT in blood plasma during stress (4,39,40). Arecent study (41) reported increased OT levels in cerebrospinal fluid, accompanied by increased plasma OT alter different kinds of stress suggesting that cerebrospinal fluid hormone levels reflect to some degree the neurosecretory…”
Section: Discussionmentioning
confidence: 99%